Over a million students use our free study notes to help them with their homework
Firstly, we need to express 6cos(2x) + sin(x) in terms of sin(x) 6cos(2x) + sin(x) = 6cos(x+x) + sin(x) = 6cos2(x) - 6sin2(x) + sin(x) (applying cos(x+y) = cos(x)cos(y) - sin(x)sin(y...
x2 +2xy–3y2+16=0Differentiate the terms:x2 gives 2x2xy is differentiated by the product rule: vu' +v'u Make v = 2x and u = y, which gives 2x(dy/dx) + 2y3y2 give...
x=4, y=-2
3x + 1 = 4(2x) 3x + 1 = 8x 1 = 5x x = 1/5
f(x) = x4- 4x3+ 4x2 Given the function above, we need to find its stationary points. Its stationary po...
←
457
458
459
460
461
→
Internet Safety
Payment Security
Cyber
Essentials